Scaup Depredation on Arkansas Baitfish and Sportfish Aquaculture. (21st September 2021) - Clements, Stephen A.; Dorr, Brian S.; Davis, J. Brian; Roy, Luke A.; Engle, Carole R.; Hanson‐Dorr, Katie C.; Kelly, Anita M.
ABSTRACT: Lesser scaup ( Aythya affinis ) and greater scaup ( A. marila ), hereafter scaup, consume a variety of aquatic invertebrates, plants, and occasionally small fish. Scaup have foraged on commercial aquaculture farms in the southern United States for decades. However, the types, abundance, and rate of fish exploitation by scaup on baitfish and sportfish farms are not well documented. Thus, information is needed to understand how fish and other foods influence scaup use of aquatic resources, and any potential economic effects of depredation of fish. From November–March in winters 2016–2017 and 2017–2018, we conducted 1, 458 pond surveys to estimate the abundance and distribution of scaup on Arkansas baitfish and sportfish farms that commercially produce species such as golden shiners ( Notemigonus crysoleucas ), fathead minnows ( Pimephales promelas ), goldfish ( Carassius auratus ), and sunfish ( Lepomis spp.). We also collected and processed 531 foraging scaup and quantified the proportion of scaup consuming fish and the proportion of their diet obtained from fish. Fish consumption was highly variable between years. In our survey area, we estimated total fish consumption at 1, 400 kg and 60, 500 kg for winters 2016–2017 and 2017–2018, respectively. Sunfish ponds experienced the maximum loss (18, 000 fish/ha) during winter 2017–2018, while goldfish ponds experienced a loss of just 2, 600 fish/ha during the same winter. The estimates of baitfish and sportfish loss to scaup revealed potential management strategies for minimizing fish loss and can inform economic analysis of the financial impact of scaup on producers. © 2021 The Wildlife Society. Abstract : Scaup can consume substantial amounts of baitfish grown on Arkansas aquaculture farms, but there is considerable inter‐annual variability in depredation severity. We suggest that producers consider other factors (e.g., winter temperatures) when deciding on resources to allocate toward bird harassment.